(untitled) (TAMADDUN NURI JURNALI, 2025)
This article explores the multifaceted views of the prominent medieval Sufi scholar, theorist of Sufism, and hadith expert Abu Ishaq Kalabadi on the disciplines of Sufism and hadith. It highlights the distinctive characteristics of his approach to these religious sciences. Particular attention is given to the contribution of the Bukhara scholarly tradition to the development of hadith studies, as well as the harmonious integration and interconnection between hadith and Sufism. The analysis is based on a comparative study of Sufi texts.